Urban Agglomerations and Methods of Delimitation - Egamberdieva Matluba Mamanazarovna; Jo’rayev Sherzod Sultanbayevich; Khakimova Kamola Rakhimjonovna (Zien Journals, 2024)
The article presents the existing approaches to defining the boundaries of urban agglomerations, and the debatable state of this issue is noted. The authors analyzed the current options for the delimitation of urban agglomerations in various countries
Keywords: urbanization; agglomeration; delimitation methodology